Effects of near-field ground motions and soil-structure interaction on dynamic response of a cable-stayed bridge. Issue 133 (June 2020) - Tochaei, Emad Norouzzadeh; Taylor, Todd; Ansari, Farhad
Abstract: Seismic response of cable-stayed bridges is investigated with the main focus pertaining to the effects of near-field ground motions and soil-structure interaction on the dynamic response of the bridges. A 1/60 scale model of a typical cable-stayed bridge was designed and fabricated for the laboratory investigations. Three different types of ground motion records from the 1999 Chi-Chi earthquake, namely far-field, non-pulse near-field, and pulse-type near-field were employed in the experiments and the numerical analysis of the bridge. Laboratory simulation of the soil-structure interaction was accomplished by a box-spring system with interchangeable springs as foundations for the bridge towers. A three-dimensional numerical model of the bridge was developed, and its response was verified by the experimental results. Results from the numerical and experimental investigations indicated that the effects of foundation soil stiffness on the response of the bridge was influenced by the type of input ground motions. The bridge response was amplified when their foundation was in softer soils. Highlights: Effects of soil-structure interaction and near-field ground motions on cable-stayed bridges were investigated. A 1/60 laboratory scale model of the bridge was designed and fabricated for this study. A box-spring system was designed to represent the soil-structure interaction effects. The bridge response was amplified when foundation was in softer soils. Soil-structure interaction effects were amplified under near-field input ground motions.